2012
DOI: 10.1093/cid/cis424
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Pyomyositis: Report of 2 Cases and Review of the Literature

Abstract: Streptococcus pneumoniae is an uncommon cause of pyomyositis. It is unclear whether the clinical presentation and outcome of pneumococcal pyomyositis differ depending on the host's underlying immune status. We describe 2 patients with pneumococcal pyomyositis, review all published cases, and compare characteristics between apparently healthy hosts and at-risk hosts. A total of 35 cases of pneumococcal pyomyositis were identified, 11 in apparently healthy hosts and 24 in at-risk hosts. Two-thirds of the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The most common cause of PM is Staphylococcus aureus. It is suggested that trauma is a facilitating factor for microorganism invasion in patients with PM, [1][2][3][4][5] but trauma has been reported in only about 10% of PM patients (in our case there was a possibility of accidental trauma caused by the patient's brother). Thus, invasion of pneumococci to the hip muscle might be facilitated by this event during the bacteremia caused by S. pneumoniae.…”
Section: Discussionmentioning
confidence: 58%
“…The most common cause of PM is Staphylococcus aureus. It is suggested that trauma is a facilitating factor for microorganism invasion in patients with PM, [1][2][3][4][5] but trauma has been reported in only about 10% of PM patients (in our case there was a possibility of accidental trauma caused by the patient's brother). Thus, invasion of pneumococci to the hip muscle might be facilitated by this event during the bacteremia caused by S. pneumoniae.…”
Section: Discussionmentioning
confidence: 58%
“…Our findings are in line with literature data suggesting a strong correlation between infectious myositis and underlying medical conditions. 3,17,20,21 This was verified for all bacterial responsible strains even if a distinction must be made as concerns E. coli myositis. In fact, of 18 cases reported in literature up till December 2014 6,22-24 almost all patients (94%) were severely immune-compromised for malignancy (mainly hematologic) or HIV-AIDS.…”
Section: Discussionmentioning
confidence: 68%
“…Second, the patient's neck pain, serum CK and MRI abnormalities improved with antimicrobial therapy. Few cases of pneumococcal myositis have been reported (2). The previous cases involved other regions (2-4); streptococcal pyomyositis in the neck muscles is very rare.…”
Section: Discussionmentioning
confidence: 99%